2004
DOI: 10.1080/00016350410001586
|View full text |Cite
|
Sign up to set email alerts
|

Dental fear and oral health and family characteristics of Finnish children

Abstract: Fear of dental treatment is still fairly common among Finnish children, and the factors associated with it differ with the age of the child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
94
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 11 publications
12
94
2
7
Order By: Relevance
“…Th is can be explained by changes due to the growth and development of enhanced self-control and the use of a rational approach in stressful situations, such as dental procedures. Some studies have confi rmed that fear of dental treatment decreases with increasing age because children have control over the way they express fear 15,27,28 . Th is supports the idea that if children can gain experience or become familiar or accustomed with an upcoming dental procedure, then this could reduce the level of their fear and dental anxiety related to the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Th is can be explained by changes due to the growth and development of enhanced self-control and the use of a rational approach in stressful situations, such as dental procedures. Some studies have confi rmed that fear of dental treatment decreases with increasing age because children have control over the way they express fear 15,27,28 . Th is supports the idea that if children can gain experience or become familiar or accustomed with an upcoming dental procedure, then this could reduce the level of their fear and dental anxiety related to the situation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be interpreted that children who were anxious before the procedure were more likely to be distressed and affected the child in all dimensions. Rantavouri et al (2004) found that children were affected by age related dental fear in 1474 children, 3-15 years old using the Child Fear Rating Scale (CFSS-DS) in Finland. In their study, the 3-6 years age group children had more dental anxiety [37].…”
Section: Discussionmentioning
confidence: 99%
“…Rantavouri et al (2004) found that children were affected by age related dental fear in 1474 children, 3-15 years old using the Child Fear Rating Scale (CFSS-DS) in Finland. In their study, the 3-6 years age group children had more dental anxiety [37]. Taani et al (2005) found that girls were more likely to have higher levels of fear than boys on 1021 children aged 12-15 years in Jordan [ 38].Similarly, Önçağ and Çoğulu (2005) found that the dental fear level of girls was higher than in boys on 120 children aged 3-12 years who applied to the Pedodontics Clinic, using the Child Fear Rating Scale (CFSS-DS) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Kruger ve arkadaşları (31) dental korkunun çürükler için önemli bir belirleyici olduğunu belirtmişlerdir . Yapılan çalışmalarda dental korku ile çürük arasında anlamlı ilişki olduğu görülmüştür (31)(32)(33). Hägglin ve arkadaşları (34) ve Schuller ve arkadaşları (35) tarafından yapılan DMFT skorları ve anksiyete ile ilgili çalışmalarda, yüksek anksiyeteye sahip bireylerde çürük diş/diş yüzeyi ve eksik diş sayısının fazla, restore edilmiş diş sayısının az olduğu rapor edilmiştir.…”
Section: Tartiġmaunclassified